Bałkany w ujęciu historiografii kościelnej V wieku związanej ze środowiskiem konstantynopolitańskim - Bralewski, Sławomir (Vox Patrum, 2016)
In the accounts of Socrates of Constantinople, Hermias Sozomenus and Philostorgius, i.e. those ecclesiastical historians who represented the Constantinopolitan point of view in church history, the region of the Balkans was neither administratively nor culturally or religiously uniform. Contents of their works suggest, however, that the area was very important strategically, which was indirectly stressed in Sozomenus’ and Phlilostorgius’ accounts of the conflicts between Constantine and Licinius, and then directly referred to when the three historians wrote on the invasion of the Goths and Maximus’ usurpation. All the three sources also imply that the Balkan peninsula became a shelter not only for refugees from the outside of the empire but also a safe haven for political fugitives from the Roman territories, as for instance is the case of Valentinian II and his entourage. It is also clearly visible that the region was treated by the historians as the hinterland of Constantinople, i.e. the second capital of the Roman Empire, founded by order of Constantine. Security of the capital was largely dependent on the stability of the Roman rule in the Balkans and the maintenance of peace in the area. The advent of the Huns, who pushed other barbarians to cross the Danube river, destabilized the region. The destabilization occurred even despite efforts of christianizing the inflowing tribes, which was an element of the strategy of the Romans targeted at subjecting the barbarian peoples to the empire both politically as well as religiously. Socrates’, Sozomenus’ and Philostorgius’ accounts also show that the Balkans became a border zone of the empire (divided into its western and eastern parts) and a melting pot of various religious influences, which is exemplified by the regional history of Arianism. It is also undeniable that not only Socrates of Constantinople and Hermias Sozomenus but also Phlostorgius devoted to the Balkans more attention than Eusebius of Caesarea did. The fact can be explained on he basis of their geographical proximity to the region, which naturally drew the interest of the former, Constantinopole-based three. Last but not least, Sozomenus displayed in his narrative a better geographical competence as for the region than Socrates and therefore he tried to emend the account of his predecessor.